Analisis Faktor-Faktor Penyebab Keterlambatan Penyerapan Anggaran (Studi Kasus Pada Balai Besar Wilayah Sungai Citarum Kementerian PUPR) - Syafira Rizka Nurwidya; Vina Citra Mulyandani (Indonesian Accounting Research Journal, 2020)
Central government spending is the largest component in terms of state spending and has an important role in determining national output. Ideally, the increase in state expenditure can follow a responsive absorption pattern both in central government spending and for transfers to regions. The absorption of the accumulated budget at the end of the year indicates that budget execution is not yet optimal. Fiscal year 2018 in Balai Besar Wilayah Sungai Citarum (BBWS Citarum) not performed optimally. The delay in budget absences is too high at Balai Besar Wilayah Sungai Citarum (BBWS Citarum). This study aims to analyze the factors that cause budget shortages at Balai Besar Wilayah Sungai Citarum (BBWS Citarum) for the 2018 fiscal year. This research uses a credibility test with triangulation techniques. The research method used is a qualitative method. The results shows that the budget allocation in the 2018 fiscal year was caused by four factors, namely planning, implementation, human resources, and goods / services procurement.